2021
DOI: 10.3389/fmed.2021.731911
|View full text |Cite
|
Sign up to set email alerts
|

Human CLA+ Memory T Cell and Cytokines in Psoriasis

Abstract: Psoriasis is a common inflammatory skin condition resulting from the interplay between epidermal keratinocytes and immunological cellular components. This sustained inflammation is essentially driven by pro-inflammatory cytokines with the IL-23/IL-17 axis playing a critical central role, as proved by the clinical efficacy of their blockade in patients. Among all the CD45R0+ memory T cell subsets, those with special tropism for cutaneous tissues are identified by the expression of the Cutaneous Lymphocyte-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
5
0
2
Order By: Relevance
“…41,42 A potential factor that might influence the results reported here is possible recirculation of T cells from the skin back into the blood. This concept of recirculation has been postulated several times [43][44][45] based on observations from clinical trials with LFA-1 antibodies to block skin infiltration. 46,47 These studies observed accumulating and bona fide recirculating T cells in the blood, which were CLA + .…”
Section: Aeroallergen-specifictcellsarepartofthe Ad Skin Infiltratementioning
confidence: 99%
“…41,42 A potential factor that might influence the results reported here is possible recirculation of T cells from the skin back into the blood. This concept of recirculation has been postulated several times [43][44][45] based on observations from clinical trials with LFA-1 antibodies to block skin infiltration. 46,47 These studies observed accumulating and bona fide recirculating T cells in the blood, which were CLA + .…”
Section: Aeroallergen-specifictcellsarepartofthe Ad Skin Infiltratementioning
confidence: 99%
“…It is known that CLA, encoded by gene SELPLG , positive memory T cells distribute in a large number in psoriatic lesions, and CLA is the molecular basis for mediating cell chemotaxis to skin lesions ( 17 , 18 ). In order to explore the ideal metabolic intervention of immunometabolism reprogramming of PSO, we performed analysis at the level of Cluster_T cells and skin-homing subfractions CLA+T cells, focused on subset of CD4+ TCMs, CD8+ TEMs, Tregs, MAITs, and γδ T cells.…”
Section: Resultsmentioning
confidence: 99%
“…In male rats, polysaccharide-degrading bacteria were mainly dominated by Bacteroidia , such as Muribaculaceae ( 64 ), which could increase the expression of AhRR in intestinal immune cells as well as Bacteroides which could synthesize conjugated linoleic acid (CLA). The latter can regulate immune functions, lower blood lipids and exert anti-diabetic as well as anti-inflammatory effects ( 65 , 66 ).Through comparative analysis examining how dominant bacteria varied between sexes after consuming IOP, it was found that IOP could improve the activity of dominant bacteria in intestinal microbes, and these results could form the basis of a future approach whereby bacterial species are selected based on sex-related differences to reshape the intestinal microenvironment, while providing ideas for metabolic analysis.…”
Section: Discussionmentioning
confidence: 99%